Organisasi Pembelajar Pada Biro Organisasi Tata Laksana Sekretariat Daerah Provinsi Sulawesi Barat - S, Muhammad Akbar; Salman, Rara Novrayanti (Jurnal Ilmiah Multidisiplin Amsir, 2024)
Learning organizations have not gone well because complaints about bureaucratic performancestill color in every service provided by the government. This study aims to see the implementationof discipline of the five learning organizations according to peter senge to determine the strategyof organizational performance improvement. This study used a quantitative approach with asample of 31 employees selected by sample saturated. Data were collected throughquestionnaires, observations and documentation. Descriptive statistical analysis used for dataprocessed into tables and interpreted through observation and documentation. The results of thestudy indicate that of the five disciplines of the learning organization are (1) Personal skills 3.04including good category (2) Mental model 3.13 including good category (3) Shared vision 3.05including good category (4) Teaching 3, 15 including good category (5) Thinking 3.09 system isgood category. The five disciplines have an average grade of 3.09 including either category. It isconcluded that the five disciplines of learning organizations already exist and generally run wellbut there are still employees who are less able to apply due to low morale to learn new things andleadership commitment in creating a learning organizational climate so that employees alwayswant to increase the capacity individually or as a team.